2019
DOI: 10.3390/catal9020137
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characteristics of Vehicle-Aged Heavy-Duty Diesel Oxidation Catalyst and Natural Gas Three-Way Catalyst

Abstract: Techniques to control vehicle engine emissions have been under increasing need for development during the last few years in the more and more strictly regulated society. In this study, vehicle-aged heavy-duty catalysts from diesel and natural gas engines were analyzed using a cross-sectional electron microscopy method with both a scanning electron microscope and a transmission electron microscope. Also, additional supporting characterization methods including X-ray diffractometry, X-ray photoelectron spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The complexity of catalyst poisoning obviously increases along with the increasing use of biomass/waste-derived/residual feedstocks [2,3] and with requirements for cleaner and novel sustainable processes, such as those implementing a catalytic assisted chemical looping approach [4,5].This Special Issue provides insight for several specific scientific and technical aspects of catalyst poisoning and deactivation, proposing more tolerant catalyst formulations and exploring possible regeneration strategies. In particular, 14 research articles focus on heterogeneous catalysts by investigating thermal [6-8], physical [9,10] and chemical [11][12][13][14][15][16][17][18][19] deactivation phenomena, and also exploring less conventional poisons related to the increasing use of bio-fuels [17]. Some regeneration strategies [11,16], together with solutions to prevent or limit deactivation phenomena [7,9,11,16], are also discussed.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The complexity of catalyst poisoning obviously increases along with the increasing use of biomass/waste-derived/residual feedstocks [2,3] and with requirements for cleaner and novel sustainable processes, such as those implementing a catalytic assisted chemical looping approach [4,5].This Special Issue provides insight for several specific scientific and technical aspects of catalyst poisoning and deactivation, proposing more tolerant catalyst formulations and exploring possible regeneration strategies. In particular, 14 research articles focus on heterogeneous catalysts by investigating thermal [6-8], physical [9,10] and chemical [11][12][13][14][15][16][17][18][19] deactivation phenomena, and also exploring less conventional poisons related to the increasing use of bio-fuels [17]. Some regeneration strategies [11,16], together with solutions to prevent or limit deactivation phenomena [7,9,11,16], are also discussed.…”
mentioning
confidence: 99%
“…Solutions to prevent the irreversible thermal deactivation of Ni/ZrO 2 catalysts during the Dry Reforming of Methane are proposed in [7] by inhibiting the transition of ZrO 2 into its monoclinic phase via modification with La. For the same reaction, it is well known that coke deposition is often the main cause of the deactivation of Ni-based catalysts-in [10], the authors report on the beneficial addition of barium to NiLa-based catalysts obtained from perovskite precursors to depress coke formation.Novel La-oxysulfate/oxysulfide oxygen carrier materials promoted with small amounts of Co, Mn or Cu are presented in [8], assessing their reactivity and stability during the cyclic operation of a Chemical Looping Combustion process fueled with either hydrogen or methane.Experimental data for the ageing and deactivation effects in real-life catalysts are generally scarce in the open literature, so the insight on industrial catalysts operated in full-scale systems in [9,11,15] is an important contribution. In particular, transient operations of the industrial reactor, such as shutdowns with insufficient air purging, are identified to cause an unusual deactivation behavior of a commercial V 2 O 5 /TiO 2 catalyst used for the production phthalic anhydride, as a consequence of excessive vanadium reduction and coke deposition [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations